Design of variable screw pitch rib snapping roller and residue cutter for corn harvesters - Gang, Wang; Honglei, Jia; Lie, Tang; Jian, Zhuang; Xinming, Jiang; Mingzhuo, Guo (International Journal of Agricultural and Biological Engineering, 2016)
The blocking between two snapping rollers will seriously constrict the harvesting efficiency for corn harvester. A variable screw pitch rib snapping roller was developed to solve this problem. The comparative experiment between fixed screw pitch rib snapping rollers and variable screw pitch rib snapping rollers illustrated that variable screw pitch ribs can avoid corn-stalk blocking effectively, and it can improve working efficiency by 56.7%. Conservation tillage with standing corn residue was testified that it had a strong control of soil wind erosion. In order to implement this mode of conservation tillage at a production scale, a cutter was developed in this study. Subsequently, two experiments were conducted, one was to test the cutting ratio (defined as the totally cut off stalk population divided by total stalk population), and the other one was to test standing-residue height. The experiment results showed that the mean cutting ratio increased significantly (p < 0.05) along with increasing height of cutter-head above the ground (cutting height); the cutting ratio’s mean value increased significantly (p < 0.05) along with the decreasing angle between the cutter-head and the ground (cutting angle). The average standing-residue height increased along with the increase of cutting height from 300 mm to 500 mm. The average standing-residue height increased significantly (p < 0.05) along with the decrease of cutting angle from 15° to 0°. Therefore, the newly designed snapping roller can improve the harvesting efficiency and prolong the working life of the cutting table; and the cutter can promote the popularization of the conservation tillage with standing corn residue in Northeast China.Keywords: corn harvester, variable pitch, snapping roller, standing corn residue, field imitating experiment, cutting height, cutting angleDOI: 10.3965/j.ijabe.20160901.1941Citation: Wang G, Jia H L, Tang L, Zhuang J, Jiang X M, Guo M Z. Design of variable screw pitch rib snapping roller and residue cutter for corn harvesters. Int J Agric & Biol Eng, 2016; 9(1): 27－34.